Landscape change in the Nile Delta during the fourth millennium BC: a new perspective on the Egyptian Predynastic and Protodynastic periods. Issue 4 (7th August 2020) - Pennington, Benjamin T.; Wilson, Penelope; Sturt, Fraser; Brown, Antony G.
ABSTRACT: The role environmental change may have played at the dawn of Egyptian history has been overlooked in comparison with other periods. Natural landscape changes taking place in the Nile Delta are argued here to have been a facilitating factor allowing, and possibly stimulating, socioeconomic changes leading to the 'Lower Egyptian – Naqada Transition' (LE-NT, c . 3350 BC). In this context, the LE-NT may be understood in terms of regional elites using newly agrarian delta lands as an agricultural resource and trade route, with the emerging capital, Memphis, ideally situated. We argue (almost counter-intuitively) that a natural reduction in overall landscape productivity led to agricultural intensification through a positive feedback loop. This may have laid the foundations for the emergence of a more unified Egyptian state beginning c . 3100 BC. Through this analysis, we argue for the incorporation of the environment as an integral component of change narratives of Predynastic Egypt.